Polyploid induction of Allium ascalonicum L. by colchicine - SUMINAH SUMINAH; SUTARNO SUTARNO; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2002)
The low production rate of shallot (Allium ascalonicum L.) in Indonesia could be caused by rarely excellent cultivars.Colchicine was one of the mutation agents frequently used in plant breeding in order to get polyploidy of cultivars. The aim of this research was to find out the differentiation of morphometric evidences and ploidy of shallot chromosomesinduced by colchicines 1%. Preparation was made by squash method and stained by acetocarmine. The results indicated that the amount, length and shape of chromosomes altered by the application of the agent. The polyploids produced could be grouped into tetraploids, pentaploids, hexaploids, octaploids, and nonaploids.Â© 2002 Jurusan Biologi FMIPA UNS SurakartaKey Words: chromosome, polyploids, Allium ascalonicum L., colchicines.